Melting and thermodynamic properties of rare gas nanocrystals - Karasevskii, A.I.; Lubashenko, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
A self-consistent statistical method [Phys. Rev. B66, 054302 (2002)] is used to describe thermodynamic properties of free rare gas nanocrystals using thin plates as examples. It is shown that size influence on thermodynamic properties of nanocrystals is caused by size-dependent quantization of the vibration spectrum affecting the parameters of a statistical distribution function of atomic displacements and, thus, governing size dependence of average values of energetic contributions to the Gibbs free energy of the system. For Xe nanocrystals, we present calculated size dependences of the Debye temperature, heat capacity, interatomic distance, melting temperature, etc.